(untitled) (Nordic Journal of Practical Theology, 2025)
The article examines 44 sermons delivered in the Church of Norway and asks what makes a sermon feel existentially important to listeners in our time. Based on Jan-Olav Henriksen’s theories of hermeneutic experience and Hartmut Rosa’s theories of resonance, it contributes to the understanding of an existential oriented homiletic theology. The analysis shows that the sermons direct attention to questions that concern life here and now, rather than traditional themes such as sin and grace, or eternal life. Such concepts are not absent or without significance. But instead of using images from human life to illustrate or explain a divine reality, the tendency is for the sermons to use theological motifs to interpret the life people live now. The sermons with the strongest rhetorical dynamics are those that reflect a resonant relationship to people’s experiential reality and at the same time show what is existentially at stake